Initial Sputum Smear Grading Is a Predictor of Smear Conversion and Treatment Outcome in Pulmonary Tuberculosis: A Retrospective Cohort Study - Das, Palash; Mondal, Ranjana; Sarkar, Kumaresh Chandra; Ghoroi, Supriti; Sarkar, Piyali; Biswas, Sukanta (National Journal of Community Medicine, 2016)
Background: Tuberculosis is an important public health problem. The Smear Conversion Rate (SCR) is an operational indicator for the Directly Observed Treatment Short course strategy of Revised National Tuberculosis Control Programme (RNTCP) in India. This study was conducted to determine the initial sputum smear grading and to assess the smear conversion rate (SCR) and treatment outcome. Materials and Methods: This retrospective cohort study was conducted among 341sputum smear positive patients from tuberculosis units of North 24 Parganas district. Record of initial smear grading, conversion and outcome of all new sputum smear positive patients were utilized. All patients were followed up periodically under the RNTCP guidelines. Result: Total numbers of newly diagnosed smear positive TB patients collected were 341.Among them sputum grading were high positive cohort (3+) 24.6% and low positive cohort (scanty, 1+ and 2+) 75.4%. The conversion rates were observed for Scanty, 1+, 2+ and 3+ at 81.7%, 82.2%, 76.5% and 52.4% respectively at the end of the intensive phase of the treatment. It has been estimated that approximately 50% of mycobacterial load was reduced after intensive phase in high grading cohort whereas it was more than 75% reduction in low grading cohort. Conclusion: The conversion rate of sputum smear was found dependent on initial sputum grading. The conversion rate was low in high grade cohort but increase in low grade cohort. The conversion rate was probably decreased on high mycobacterial load.